THE CORRELATION OF PARENTING STYLE WITH COGNITIVE DEVELOPMENT IN CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER - Dwi Fitri Genisti; Ni Komang Sukra Andini; Ni Luh Gede Puspita Yanti (Belitung Nursing Journal, 2018)
Background: Child development is a very important phase, in which children learn various skills as future generations. One of disorders that can impede child development process is Attention Deficit Hyperactivity Disorder (ADHD). Children with ADHD have problems with cognitive abilities, of which about 20-60% of them have learning disorders. The efforts to support cognitive development in children with ADHD is by approaching the child's environment through parenting style. Objective: This study aimed to determine the correlation of parenting style with cognitive development in the children with ADHD in SLB Negeri 1 Denpasar, Bali, Indonesia. Methods: This study used a correlational design with cross sectional approach. The sample size of 30 respondents were selected using a purposive sampling technique. Data were collected using parenting style questionnaire (PSQ) and average value of odd semester report of 2016/2017 academic year. Results: It was found that most parents with democratic parenting style were 19 people (63.3%), authoritarian style were 7 people (23.3%), and permissive style were 4 people (13.3%). The result of the contingency coefficient test obtained p-value of 0.039 (p <0.05) and correlation value of 0.501, which indicated that there was a high correlation between parenting style with cognitive development in children with ADHD. Conclusion: It is suggested that parents of ADHD children should be able to provide good parenting style for their children, especially for the cognitive development.